Dispositional mindfulness is associated with lower smartphone addiction through digital life balance among Chinese university students - Aldbyani, Aamer; Wang, Guiyun; Chuanxia, Zhang; Alhimaidi, Afnan (Frontiers in Psychology, 2025)
BackgroundPrior research links mindfulness to lower levels of several addictive behaviors; however, the mechanisms for smartphone use remain less clear.MethodThis cross-sectional study examined the association between dispositional mindfulness and smartphone addiction and tested the mediating role of digital life balance among 1,241 Chinese university students. Participants completed validated Chinese versions of the MAAS, SAS, and DLBS.ResultsCorrelation analyses showed that dispositional mindfulness was negatively associated with smartphone addiction (r = –0.41, p < 0.05) and positively associated with digital life balance (r = 0.45, p < 0.05). Mediation analysis using PROCESS (Model 4, 5,000 bootstrap samples) indicated a significant indirect effect of dispositional mindfulness on smartphone addiction through digital life balance (indirect effect = −0.18, SE = 0.019, 95% CI [−0.22, −0.14], while the direct effect remained significant (β = –0.23, p < 0.05).DiscussionThese results indicate an indirect association in cross-sectional data, consistent with the possibility that digital life balance partly explains the link. The study provides evidence regarding the psychological processes linking dispositional mindfulness and technology use, suggesting potential applicability of promoting digital life balance as a strategy for addressing smartphone overuse.